2022
DOI: 10.1002/rcs.2453
|View full text |Cite
|
Sign up to set email alerts
|

Robotic single‐port surgery: Preliminary experience in general surgery

Abstract: Background We aim to analyse the safety and feasibility of the DaVinci Single Port (SP) platform in general surgery. Methods A prospective series of robotic SP transabdominal pre‐peritoneal inguinal hernia repairs (SP‐TAPP) and cholecystectomies (SP‐C) (off‐label) were analysed. Primary endpoints were safety and feasibility defined by the need for conversion and incidence of perioperative complications. Results A total of 225 SP procedures were performed; 84 (37.3%) SP‐TAPP (70 unilateral, 7 bilateral), and 14… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 66 publications
(150 reference statements)
2
14
0
Order By: Relevance
“…Further, the surgeon can perform multi‐quadrant surgery without repositioning the operating room table and almost no clashing of the instruments. Similar favourable ergonomics, positioning and outcomes have been reported using SP robotics in thoracic, hernia, gynaecological and urological surgery [38–41].…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Further, the surgeon can perform multi‐quadrant surgery without repositioning the operating room table and almost no clashing of the instruments. Similar favourable ergonomics, positioning and outcomes have been reported using SP robotics in thoracic, hernia, gynaecological and urological surgery [38–41].…”
Section: Discussionsupporting
confidence: 65%
“…Further, the surgeon can perform multi-quadrant surgery without repositioning the operating room table and almost no clashing of the instruments. Similar favourable ergonomics, positioning and outcomes have been reported using SP robotics in thoracic, hernia, gynaecological and urological surgery[38][39][40][41].This work adds to the literature as there are few reports of SP robotic CRS. All published work has very small numbers with no follow-up, showing only initial safety and feasibility.…”
supporting
confidence: 72%
“…The reported cases belonged to several specialties: hepatopancreatobiliary surgery [13,[37][38][39][50][51][52][53][54][55]78,79,[87][88][89][90][91][92][93][94][95][96][97][100][101][102][103] (Tables S1 and S2), colorectal surgery [14-36,56- The authors belonged to institutions located in: South Korea (n = 27), China (n = 16), North America (n = 13), Lithuania (n = 11), Japan (n = 8), Germany (n = 6), Italy (n = 6), United Kingdom (n = 6), India (n = 4), United Arab Emirates (n = 2), Taiwan (n = 1), France (n = 1), Croatia (n = 1), Australia (n = 1).…”
Section: Resultsmentioning
confidence: 99%
“…After the da Vinci SP robotic platform from Intuitive company was approved in 2014, SP robotic surgery has shown feasibility in cholecystectomy and colectomy. [6][7][8][9] However, although the TAPP approach has been reported with a robotic system, TEP using the da Vinci SP platform has not been applied to inguinal hernia, the most common disease among surgical areas. 7 The reason for this is that in order to optimize the wrist ergonomics of the da Vinci SP platform, a certain distance from the target must be maintained.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8][9] However, although the TAPP approach has been reported with a robotic system, TEP using the da Vinci SP platform has not been applied to inguinal hernia, the most common disease among surgical areas. 7 The reason for this is that in order to optimize the wrist ergonomics of the da Vinci SP platform, a certain distance from the target must be maintained. A study that performed a da Vinci SP robotic cholecystectomy suggested need for a 10 cm distance.…”
Section: Discussionmentioning
confidence: 99%